Determining the Performance of Apis Mellifera Bandasii Populations under Different Agro-Ecologies of Central Ethiopia - Tadele Hunde; Zewdu Hora (Advances in Agriculture)
Honeybee colonies exhibit a wide range of variations in their performance, depending on genetic and environmental factors. However, there has been little research carried out on Apis mellifera bandasii (A. m. bandasii) populations to characterize their behavioural performance. To gain insight into the details of the behavioural performance of this local honeybee, we characterized and compared the colony performance of honeybee populations at different altitudes. Fifty honeybee colonies per site, making a total of 150 colonies, were established at Bako (mid-highland), Gedo, and Holeta (highland). The colonies were evaluated for brood-rearing activities, resource collecting, brood solidity, swarming, defensive and hygienic behaviours, and honey yield parameters. The average brood areas were determined to be 6114.13 ± 500.36, 3298.30 ± 365.92, and 2521.23 ± 244.67 cm2 per colony; the average nectar areas were found to be 3399.46 ± 738.88, 1238.78 ± 228.96, and 1883.09 ± 232.57 cm2 per colony; the average number of queen cells was determined to be 0.62 ± 0.30, 1.20 ± 0.39, and 2.19 ± 0.49 per colony; the average percent of pin-killed broods removed was determined to be 93.78 ± 1.74, 96.42 ± 1.86, and 80.09 ± 7.86 per colony; the average percent of colonies absconded was determined to be 36, 54, and 46 per site at Holeta, Gedo, and Bako, respectively. The mean differences among the locations for brood areas, nectar areas, number of queen cells, percent of pin-killed broods removed, and percent of colonies absconded were significant (p<0.05), while the variations in the area of stored pollen, brood solidness, and honey yield were not significant. Significant variation within colonies of the same apiary of the same subspecies was observed. These results showed that A. m. bandasii at Holeta had the best performance and that Bako had the lowest performance. Therefore, the variability in colony performances indicates the possibility of improving strains of native stocks through selection and breeding strategies using the variations as an opportunity.